Reactive histiocytosis of the orbit and posterior segment in a dog. (31st July 2012) - Pumphrey, Stephanie A.; Pizzirani, Stefano; Pirie, Christopher G.; Sato, Amy F.; Buckley, Faith I.
Abstract: We present a case of reactive histiocytic disease involving the orbit, optic nerve, retina, and choroid in a Border Collie dog initially presenting for vision loss. Long‐term partial return of vision has been achieved with systemic immunosuppression. Anterior segment and ocular surface manifestations of reactive histiocytic disease in dogs are relatively common. Posterior segment and orbital involvement, however, are minimally documented in the existing literature. To the authors' knowledge, this is the first report of disease confined to the orbit and posterior segment as well as the first report of vision loss as a presenting complaint for reactive histiocytic disease. Clinical, magnetic resonance imaging, cytologic, and histopathologic findings are reviewed.